PENGARUH GENDER, PEMAHAMAN PERPAJAKAN DAN RELIGIULITAS TERHADAP PERSEPSI PENGGELAPAN PAJAK - ULI, DESTI MONIKA; ZURMAN, ZURMAN (Fakultas Ekonomi Universitas Islam Indragiri, 2024)
To improve the well-being of the community, the government has various national development programs, one of the sources of funding is taxes. It takes the awareness of taxpayers to pay taxes. However, due to differences in views with the government, tax evasion has occurred. Tax evasion committed by taxpayers aims to minimize the amount of tax payable by violating applicable regulations. Perceptions of tax evasion are influenced by various factors, including gender, religiosity, and understanding of taxation. This study aims to determine the effect of gender, understanding of taxation, and religiosity on the perception of tax evasion. This research was conducted in Pekanbaru. The sample determination used an accidental sampling approach which made anyone who met the researcher determined as a respondent on the condition that they met the criteria as an individual taxpayer who had an NPWP. Respondents totaled 50 people. The analysis technique used uses multiple linear analysis with the help of the SPSS version 27 application. The results of the study prove that statistically understanding taxation and religiosity has a significant effect on the perception of tax evasion.